The results of combined immunotherapy in integrated treatment of patients with malignant brain glioma - V. V. Stupak (Bûlleten' Sibirskoj Mediciny, 2008)
The problem of search and development of new approaches to integrated treatment of patients with malignant brain glioma remain one of the most urgent issues for contemporary neurosurgery and neurooncology. In spite of the applied efforts the results of a complex therapy for malignant glioma, especially for glioblastoma, are utterly unsatisfactory. Immunotherapy is one of the directions searching for a generation of cytotoxic cells able to lyse the tumor. Combination of various immunotherapeutic approaches is regarded the most perspective way. Since 1999 Neurosurgical Clinic of Novosibirsk Research Institute of Traumatology and Orthopaedics was carrying out clinical trials of combined immunotherapy within complex therapy of patients with malignant brain glioma in compliance with two protocols.